Determinants of non-performing loans: emperical study on Malaysian Islamic banks - Ooi, Aaron Wei Ping (2018)
Non-performing Loans (“NPL”) has been studied by many due to its connection to financial crisis. At the same time, Islamic banking is rapidly growing throughout the years due to its many advantages. Understanding the determinants of NPL in Islamic banking will benefit not only regulators who needs to keep the stability of the banking system but also the society as well. Fixed Effect Model is used to estimate panel data from 16 Islamic banks in Malaysia from 2006 to 2015. Results of Overall study which combines data from both Foreign Islamic and Local Islamic banks shows 3 macroeconomic variables i.e. House Price Indicator, Gross Development Product and Interest Rate which are control for the changes in economic and monetary policy to be insignificant towards NPL. This supports the idea of Islamic banking being resilient to economic environment due to its profit and risk sharing nature. In terms of bank specific variable, Size shows negative relationship where bigger banks are expected to have lower NPL, Capital Adequacy relates negatively towards NPL showing shareholders of the banks being more prudent in lending, Diversification lower NPL as more non-credit based income increases the bank bottom line & lessen the pressure on credit risk at the same time and lastly loan portfolio related to real estate & variable interest rate loans have a positive & negative relationship with NPL respectively due to the lending environment in Malaysia. This study also found conflicting results between Foreign and Local Islamic banks as well as Overall result pointing out difference in credit evaluation, product offering, customer base and management style of Foreign banks.